2008
DOI: 10.1111/j.1365-2311.2007.00958.x
|View full text |Cite
|
Sign up to set email alerts
|

Migration patterns and functional groups of spiders in a desert agroecosystem

Abstract: 1. Arthropods living in annual crops suffer mortality caused by agricultural practices. Therefore, migration from surrounding habitats is crucial to maintain populations of natural enemies of insect pests in crops. In desert agroecosystems there is a pronounced contrast between managed and unmanaged habitats, where irrigated and fertilised crops are islands of productivity in an arid matrix. This contrast could either enhance or inhibit movement of natural enemies between the landscape components.2. The import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
37
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 41 publications
5
37
1
Order By: Relevance
“…In Europe, Linyphiidae benefit from a high percentage of non-crop habitats in the landscape, which serve as their winter refuge SchmidtEntling and Dö beli, 2009). In contrast to these findings, Linyphiidae in the northwest Negev clearly preferred cropland over natural semi-desert (Pluess et al, 2008;Gavish-Regev et al, 2008). Nonetheless, they did not benefit from higher percentages of crops in the landscape matrix investigated here.…”
Section: Discussioncontrasting
confidence: 53%
See 3 more Smart Citations
“…In Europe, Linyphiidae benefit from a high percentage of non-crop habitats in the landscape, which serve as their winter refuge SchmidtEntling and Dö beli, 2009). In contrast to these findings, Linyphiidae in the northwest Negev clearly preferred cropland over natural semi-desert (Pluess et al, 2008;Gavish-Regev et al, 2008). Nonetheless, they did not benefit from higher percentages of crops in the landscape matrix investigated here.…”
Section: Discussioncontrasting
confidence: 53%
“…In our study system, no landscape effect was found for Linyphiidae, and Theridiidae responded most strongly at small to medium scales, suggesting that aerial dispersal in these families is less common in the Negev Desert. Nevertheless, in the study by Gavish-Regev et al (2008), theridiid colonisation of a wheat field was consistent with dispersal by ballooning. This highlights the need for studies of spider ballooning in semi-desert regions (Bell et al, 2005).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…1), the model estimates suggest that a higher proportion of the spider population in wheat are recruited for crop immigration than in remnant vegetation. This result is in line with observations that crops are often dominated by spider species that have the ability to disperse by ballooning (Pearce et al 2005;Gavish-Regev et al 2008, Pluess et al 2008 and that the ballooning propensity is higher in spiders originating from disturbed habitats, such as crops, than from undisturbed habitats, such as remnant vegetation (Entling et al 2011). Furthermore, increased spider ballooning from wheat crops could have been triggered by wheat harvest, which coincided with the time that the experiment was conducted.…”
Section: Discussionsupporting
confidence: 75%